Gender Justice in Husband and Wife Relations According to Shaykh Nawawi Al-Bantani: A Study of the Kitab Syarah ‘Uqūd al-Lujain - Rosyada, Amrina; Mualifah, Lisna; Maliki, Ibnu Akbar (Qanun: Jurnal Hukum Keluarga Islam, 2024)
The existence of a patriarchal culture causes women to experience a double burden in the division of roles in the household. Ironically, this culture is often perpetuated through gender-biased religious interpretations. Kitab Syarah ‘Uqūd al-Lujain by Syaikh Nawawi al-Bantani is one of the classic books that responds to the injustice of women in the household. This article aims to examine the concept of gender justice according to Syaikh Nawawi al-Bantani taken from Kitab Syarah ‘Uqūd al-Lujain. The gender approach is used to analyse the division of rights and obligations of husband and wife in the book. This research uses the library research method, with the main data in the form of Kitab Syarah ‘Uqūd al-Lujain fi Bayān Huqūq al-Zaujain, as well as secondary data which includes books, journal articles, theses, and theses relevant to the research theme. The results show that according to Syaikh Nawawi al-Bantani, the rights and obligations of husband and wife are balanced, although not functionally equal because each has its own portion. The rights of wives include: being treated well and not being hurt, providing for daily needs (physically and mentally), gentle and patient treatment, and obtaining education about religious knowledge. Meanwhile, the husband's rights that must be fulfilled by his wife include being respected as the leader of the family, obtaining obedience from his wife, getting his wife's permission when leaving the house and using property, and receiving proper treatment. However, some perspectives in ‘Uqūd al-Lujain still place the wife under the husband, with the husband as the leader of the household. This is inseparable from the influence of the dynamics of the times when this book was written.